2009
DOI: 10.1242/jcs.055202
|View full text |Cite
|
Sign up to set email alerts
|

Fission yeast Myo51 is a meiotic spindle pole body component with discrete roles during cell fusion and spore formation

Abstract: Class V myosins are dimeric actin-associated motor proteins that deliver cellular cargoes to discrete cellular locations. Fission yeast possess two class V myosins, Myo51 and Myo52. Although Myo52 has been shown to have roles in vacuole distribution, cytokinesis and cell growth, Myo51 has no as yet discernible function in the vegetative life cycle. Here, we uncover distinct functions for this motor protein during mating and meiosis. Not only does Myo51 transiently localise to a foci at the site of cell fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 62 publications
(66 reference statements)
0
24
0
3
Order By: Relevance
“…However, the expression of each actin polymer labelling fusion protein we tested (i.e. GFP-CHD Rng2 , GFP-Cdc8, For3-GFP) (Doyle et al, 2009;Karagiannis et al, 2005;Martin and Chang, 2006;Skoumpla et al, 2007) rescued the naa25 strain cytokinenetic phenotypes (not shown). This not only indicates that each GFP fusion protein stabilises actin filaments and affects normal actin polymer dynamics, but suggests that the naa25 defect is brought about by instability of the actin ring.…”
Section: Resultsmentioning
confidence: 94%
“…However, the expression of each actin polymer labelling fusion protein we tested (i.e. GFP-CHD Rng2 , GFP-Cdc8, For3-GFP) (Doyle et al, 2009;Karagiannis et al, 2005;Martin and Chang, 2006;Skoumpla et al, 2007) rescued the naa25 strain cytokinenetic phenotypes (not shown). This not only indicates that each GFP fusion protein stabilises actin filaments and affects normal actin polymer dynamics, but suggests that the naa25 defect is brought about by instability of the actin ring.…”
Section: Resultsmentioning
confidence: 94%
“…1E; Dudin et al 2015). Fourth, the second type V myosin Myo51, which accumulates at the fusion focus late in the process (Doyle et al 2009;Dudin et al 2015), was detected in both cells only in committed pairs (Supplemental Fig. S1).…”
Section: A Diffusible Signal Is Necessary For Cell Fusionmentioning
confidence: 94%
“…After agglutination, the cross wall separating both parental cells is degraded, allowing cell fusion. Efficient cell fusion requires the correct organization of the cytoskeleton (Petersen et al 1995(Petersen et al , 1998aKurahashi et al 2002;Doyle et al 2009). The S. cerevisiae FUS1 and the S. pombe fus1 + genes have the same name and both mutants exhibit cell fusion defects during mating, leading to an accumulation of prezygotes (mating intermediates in which the mating partners have established a stable contact but have not yet fused).…”
mentioning
confidence: 99%